Cross-Section of Expected Stock Returns: An Application of Fama-French Five Factor Model in Nepal - Joshi, Vishal (The Batuk, 2024)
This study aimed to analyze the efficiency of Fama-French five factor model to explain cross-section stock returns in Nepalese stock market. The study adopted descriptive and analytical research design. Out of 228 firms listed in NEPSE, following judgmental sampling design, 65 firms were selected which met the sampling criteria. Panel data was collected from secondary source for the period of July 16, 2016 to July 16, 2022. Sampling frame, daily stock prices and dividends were obtained from official website of Nepal Stock Exchange (NEPSE). Firm-specific accounting data was obtained from annual reports of sample firms. 28 days weighted average Treasury bill rates were used as a proxy for risk free rate which was obtained from Economic bulletin of Nepal Rastra Bank. Three types of portfolios were constructed namely 25 Size-BM portfolios, 25 Size-ROE portfolios and 25 Size-Investment portfolios. Factor returns were created by using 2 × 3 and 2 × 2 × 2 × 2 sorting. Regression result revealed that the Fama-French five factor model is capable to capture the variation in cross-section stock returns in Nepal. Among five factors, the market risk premium found to be the most prominent factor affecting stock returns.